2016
DOI: 10.1074/mcp.m115.056580
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E*4 (APOE*4) Genotype Is Associated with Altered Levels of Glutamate Signaling Proteins and Synaptic Coexpression Networks in the Prefrontal Cortex in Mild to Moderate Alzheimer Disease

Abstract: It has been hypothesized that Alzheimer disease (AD) is primarily a disorder of the synapse. However, assessment of the synaptic proteome in AD subjects has been limited to a small number of proteins and often included subjects with end-stage pathology. Protein from prefrontal cortex gray matter of 59 AD subjects with mild to moderate dementia and 12 normal elderly subjects was assayed using targeted mass spectrometry to quantify 191 synaptically expressed proteins. The profile of synaptic protein expression c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 54 publications
2
23
0
Order By: Relevance
“…Studies of PreC in AD reported loss of total synapse numbers at the ultrastructural level (Scheff et al, 2013) and loss of postsynaptic protein PSD-95 (Gylys et al, 2004). With several notable exceptions (Sweet et al, 2016), loss of postsynaptic proteins was also reported in other cortical areas in AD. Using Western blot analysis, loss of the postsynaptic protein drebrin was reported in the superior frontal, superior temporal, and visual cortex as well as the hippocampus in mAD (Counts et al, 2006, 2012).…”
Section: Discussionmentioning
confidence: 89%
“…Studies of PreC in AD reported loss of total synapse numbers at the ultrastructural level (Scheff et al, 2013) and loss of postsynaptic protein PSD-95 (Gylys et al, 2004). With several notable exceptions (Sweet et al, 2016), loss of postsynaptic proteins was also reported in other cortical areas in AD. Using Western blot analysis, loss of the postsynaptic protein drebrin was reported in the superior frontal, superior temporal, and visual cortex as well as the hippocampus in mAD (Counts et al, 2006, 2012).…”
Section: Discussionmentioning
confidence: 89%
“…First, the significantly altered proteins in rpAD plaques were compared to our database of AD associated proteins identified in previous proteomic studies[1, 2, 4, 11, 13, 14, 22, 3133, 36, 37, 43, 45, 50, 54, 55, 66, 77, 78, 82, 89, 90, 96]. In this database we annotated proteins as up-regulated in AD, down-regulated in AD and proteins that are enriched in plaques or tangles (Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…This database combined the results from studies that identified proteins in neurofibrillary tangles[50, 66, 82], proteins enriched in plaques[32, 43], proteins that had significantly altered expression in various regions and/or fractions of AD brains in comparison to control brains and proteins that contained the keyword “Alzheimer” in the Uniprot human database[1, 2, 4, 11, 13, 14, 22, 3133, 36, 37, 45, 54, 55, 77, 78, 89, 90, 96]. Protein groups identified in rpAD and sAD plaques were screened against this database to determine how many of the proteins identified in this study have been previously associated with AD pathology.…”
Section: Methodsmentioning
confidence: 99%
“…Other recent clinical evidence also supports this result: for instance, a recent longitudinal study of CSF biomarkers found that APOE4 genotype influences dramatically markers of neuronal injury inducing a constant increase of CSF t-tau and p-tau181 levels 36 , and higher CSF tau levels were specifically correlated with increased tau in the temporal lobe, a region involved in memory processing 38 . Indeed, there is an increased risk of progression from mild cognitive impairment to AD with elevated CSF t-tau and p-tau and with the presence of the APOE4 genotype, but not with decreased CSF Aβ42 levels 39 . Moreover, APOE4 may accelerate onset of dementia and neuronal degeneration by differentially impairing the maintenance of synaptic strength and reducing glutamate signaling proteins, even in the absence of overexpression of APP and Aβ APOE4 39 .…”
Section: Discussionmentioning
confidence: 99%